From Benign to Malign in a Case of Cervical Adenopathy in a 17-Year-Old Adolescent: Diagnostic Traps - Simona Dumitra; Maria Trailescu; Amelia Burlea; Claudia Covaci; Ozana Balan; Adrian Pavel; Carmen Crișan (Case Reports in Pediatrics)
Distinguishing between benign and malign adenopathies remains a challenge and could represent a source of error in a diagnosis. We report a case of right laterocervical adenopathy in a 17-year-old teenager admitted to hospital with an episode of fever associated with dysphagia, congested pharynx, and pultaceous deposits. Initially the adenopathy was considered to be secondary to a coinfection with Streptococcus B-hemolytic and Epstein-Barr virus, as suggested by the positive bacteriological and serological tests. The onset of the adenopathy before the episode and the ultrasound modifications raised the suspicion of a malignancy, later confirmed by the histopathologic examination of the lymph node excision. The final diagnosis was nodal metastasis of an undifferentiated lymphoepithelial carcinoma with an ENT starting point. Currently, the adolescent is hospitalised in the ENT ward, where the pharynx carcinoma with nodal metastasis was confirmed. Sometimes the infectious context can mask or unmask a malign chronic disease with insidious evolution.